Globalization and the identity of the mental image structure of urban spaces (Journal of Planner and Development, 2007)
This research discusses the subject of identity in the urban environment as it attempts to answer a number of questions that come with the concept of identity. The first of these questions: What is identity? Can a definition or conceptual framework be developed for identity? What about individual, collective, cultural, ethnic, political and regional identity? Is there a definition of identity in the urban environment in particular? If there is a definition of identity, what about social mobility responsible for social change? How can we see identity through this kinetics? Can we assume that identity in the urban environment has a variable structure or is of variable shape with a more stable structure? Can we determine the spatial-temporal path to change the shape and structure of urban identity in the urban environment?